2017
DOI: 10.1038/cdd.2017.105
|View full text |Cite
|
Sign up to set email alerts
|

p53 amyloid formation leading to its loss of function: implications in cancer pathogenesis

Abstract: The transcriptional regulator p53 has an essential role in tumor suppression. Almost 50% of human cancers are associated with the loss of p53 functions, where p53 often accumulates in the nucleus as well as in cytoplasm. Although it has been previously suggested that amyloid formation could be a cause of p53 loss-of-function in subset of tumors, the characterization of these amyloids and its structure-function relationship is not yet established. In the current study, we provide several evidences for the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
191
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(205 citation statements)
references
References 59 publications
6
191
0
Order By: Relevance
“…We tested the ability of MDA-MB-231 cell lysates containing mutant p53 to induce aggregation of recombinant WT p53C, and we observed a clear seeding effect indicative of aggregates in the cell extract promoting WTp53C aggregation in a prionlike manner. This result is in agreement with the evidence for a prion-like behavior of aggregates of p53 (7,11,19,65). Lysates obtained from cells treated with PRIMA-1 had a weaker seeding capacity, which corroborates our findings of a reduction in the cellular amyloid-state p53 content after PRIMA-1 treatment.…”
Section: Discussionsupporting
confidence: 92%
“…We tested the ability of MDA-MB-231 cell lysates containing mutant p53 to induce aggregation of recombinant WT p53C, and we observed a clear seeding effect indicative of aggregates in the cell extract promoting WTp53C aggregation in a prionlike manner. This result is in agreement with the evidence for a prion-like behavior of aggregates of p53 (7,11,19,65). Lysates obtained from cells treated with PRIMA-1 had a weaker seeding capacity, which corroborates our findings of a reduction in the cellular amyloid-state p53 content after PRIMA-1 treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Supporting this hypothesis, the TAp63α that in normal conditions acquires a closed conformation in which the TI domain is inaccessible, does not interact with p53R175H [84]. Through this co-aggregation mechanism, mutant p53 proteins may exert a dominant negative effect on p63 and p73, inhibiting their functions [85][86][87]. In particular, the formation of mutant p53/p63 or mutant p53/p73 complexes has been shown to promote invasion through several mechanism.…”
Section: Effect Of Mutant P53 Gof On P53 Family Members: Tumor Invasimentioning
confidence: 96%
“…Next, we hypothesized that similar to mutant p53 (Stein et al, 2019), p53 amyloids can also act as an oncoprotein. Previously, we had demonstrated that p53 amyloids can enhance the existing transformative properties of SH-SY5Y cells (neuroblastoma cell line) (Ghosh et al, 2017). We propose that similar changes might also induce the transformation of normal cells.…”
Section: Results P53 Amyloid Formation Leads To Loss Of Tumor Suppresmentioning
confidence: 71%
“…These cells have been used to identify oncogenic agents, which can cause transformation in cells (Imbalzano et al, 2009;Scott et al, 2004;Yusuf and Frenkel, 2010). Since exogenous addition of p53 core amyloid fibrils (seeds) leads to endogenous p53 amyloid formation in cells (Ghosh et al, 2017), we have used this method to induce p53 amyloid formation in these two normal cells. For amyloid seed preparation, p53 core protein was incubated and its aggregation and amyloid formation was confirmed using Circular Dichroism (CD), Thioflavin T (ThT) fluorescence and electron microscopic imaging ( Figure 1A, S1A-C).…”
Section: Results P53 Amyloid Formation Leads To Loss Of Tumor Suppresmentioning
confidence: 99%
See 1 more Smart Citation